Evaluating the impact of using a wound‐specific oral nutritional supplement to support wound healing in a rehabilitation setting. Issue 1 (9th June 2022) - Clark, Rya K.; Stampas, Argyrios; Kerr, Kirk W.; Nelson, Jeffrey L.; Sulo, Suela; Leon‐Novelo, Luis; Ngan, Esther; Pandya, Dehuti
Abstract: Chronic wounds adversely affect patient quality of life, increase the risk of mortality, and impose high costs on healthcare systems. Since protein‐energy malnutrition or specific nutrient deficiencies can delay wound healing, nutritionally focused care is a key strategy to help prevent or treat the occurrence of non‐healing wounds. The objective of our study of inpatients in a rehabilitation hospital was to quantify the effect of daily wound‐specific oral nutritional supplementation (WS‐ONS) on healing chronic wounds. Using electronic medical records, we conducted a retrospective analysis of patients with chronic wounds. We identified records for (a) a treatment group who received standard wound care + usual hospital diet + daily WS‐ONS for ≥14 days, and (b) a control group who received standard wound care + a usual hospital diet. We collected data for demographics, nutritional status, and wound‐relevant health characteristics. We examined weekly measurements of wound number and sizes (surface area for superficial wounds or volume for non‐superficial wounds). There were 341 patients identified, 114 with 322 wounds in the treatment group and 227 patients with 420 wounds in the control group. We found that rehabilitation inpatients who were given nutritional support had larger wounds and lower functional independence on admission. At discharge, wound area reduction (percent) was nearly two‐fold better in patients who were given daily WS‐ONS + usual hospital diet compared to those who consumed usual diet only (61.1% vs 34.5%). Overall, weekly wound improvement (lowered wound area or wound volume) was more likely in the WS‐ONS group than in the Control group, particularly from the start of care to week 2. Inpatients with largest wounds and lowest functional independence on admission were most likely to be given WS‐ONS, an indication that caregivers recognised the need for supplementation. Week‐to‐week improvement in wound size was more likely in patients who received WS‐ONS than in those who did not. Specifically, wound areas and wound volumes were significantly lower at discharge among patients who were given specialised nutritional support. More research in this field is needed to improve care and reduce healthcare costs.